2017
DOI: 10.1007/s11747-017-0521-1
|View full text |Cite
|
Sign up to set email alerts
|

Are conservative approaches to new product selling a blessing in disguise?

Abstract: A new product's success in the marketplace largely depends on salesforce actions. Many B2B salespeople display conservatism when confronted with new products in their portfolio, such that they maximize their efforts to sell existing products before engaging in efforts to sell the new product. So far, it is unclear whether this conservative selling behavior (CSB) is harmful to new product selling performance, and how this behavior can be managed. Building on perceived risk processing theory, and employing multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 73 publications
0
16
0
1
Order By: Relevance
“…As previous research has shown, an important step is to establish an industry‐specific definition of “new product” that is meaningful to the survey respondents (Van der Borgh and Schepers, ). This is because product life‐cycle times and sales process durations vary substantially by industry (Nadkarni and Narayanan, ), determining which sales represent novel challenges for sales reps.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…As previous research has shown, an important step is to establish an industry‐specific definition of “new product” that is meaningful to the survey respondents (Van der Borgh and Schepers, ). This is because product life‐cycle times and sales process durations vary substantially by industry (Nadkarni and Narayanan, ), determining which sales represent novel challenges for sales reps.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in a short life‐cycle industry, such as consumer electronics, new product selling may be defined as the sale of products that are younger than six months (Van der Borgh and Schepers, ). In other industries with longer life cycles, such as information and communications technology, a longer time span is necessary for a valid and understandable definition of “new product” (Hultink and Atuahene‐Gima, ; Van der Borgh and Schepers, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations